Quality of life among survivors from building collapse: case study of Rana Plaza, Savar, Dhaka - Alve, Md. Yeasir Arafat (BRAC University, 2014)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Master in Disaster Management, 2014.